2015
DOI: 10.1186/s12889-015-1405-2
|View full text |Cite
|
Sign up to set email alerts
|

Availability of emergency obstetric care (EmOC) among public and private health facilities in rural northwest Bangladesh

Abstract: BackgroundAlthough safe motherhood strategies recommend that women seek timely care from health facilities for obstetric complications, few studies have described facility availability of emergency obstetric care (EmOC). We sought to describe and compare availability and readiness to provide EmOC among public and private health facilities commonly visited for pregnancy-related complications in two districts of northwest Bangladesh. We also described aspects of financial and geographic access to healthcare and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 16 publications
0
33
1
Order By: Relevance
“…[30][31][32] However, there were differences in the criteria used in assessing the quality of care compared with those used in a previous study, 24 that is, differences in number of signal functions for each category, no distinction of regular versus skilled health professionals, and no use of nonmedical functions.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…[30][31][32] However, there were differences in the criteria used in assessing the quality of care compared with those used in a previous study, 24 that is, differences in number of signal functions for each category, no distinction of regular versus skilled health professionals, and no use of nonmedical functions.…”
Section: Discussionmentioning
confidence: 83%
“…The lack of staff, particularly specialized staff, working in public obstetric and newborn care facilities, was also found in previous studies. 21,32 Bangladesh faces the problem of shortage of and unequal distribution of qualified staff in obstetric and newborn care. A previous study found that lack of job openings in government health facilities for nurses was a common barrier to obstetric care programs in rural Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent maternal mortality survey revealed that MMR in Bangladesh has stalled between 2010 and 2016 stagnating at 196 per 100,000 live births (BMMS 2017) .Despite the success stories, the need for professional and trained healthcare providers at rural level is still on the rise. Rural women across Bangladesh has limited access to health services during pregnancy, delivery and postpartum period due to lack of emergency obstetric care (EmOC) facilities in their vicinity, poor financial condition and limited decision-making power (Sikder et al, 2015).…”
Section: Resultsmentioning
confidence: 99%